Species sensitivity and functional uniqueness determine the response of macroinvertebrate functional diversity to species loss in urban streams - Gao, Jin; Peng, Zhiqi; Zang, Haoming; Wang, Yinchang; Ding, Ning; He, Siwen; Datry, Thibault; Wang, Beixin (Freshwater biology, 2023)
Land‐use change, particularly urbanisation, has led to an unprecedented decline in species and functional diversity worldwide. However, the mechanism through which such species loss affects functional diversity remains unclear. Here, we aimed to elucidate this mechanism from the perspectives of the association between species sensitivity and functional uniqueness (i.e., their relative contribution to functional diversity) and their related functional traits. We collected stream macroinvertebrates and measured environmental and land‐use variables from 152 sites in the highly urbanised Qiantang River Basin in the Zhejiang Province of eastern China. Firstly, we evaluated the sensitivity to urbanisation and functional uniqueness of each macroinvertebrate taxon to identify their association patterns. Secondly, we examined the decline in functional diversity in response to taxon loss by comparing simulated ordered and random taxon loss scenarios. Finally, we identified sensitivity‐related traits (SRT) and functional uniqueness‐related traits (URT) using the Mann–Whitney U‐test to elucidate their role in shaping functional response patterns to taxon loss. Urbanisation showed a remarkable effect on the taxonomic and functional diversity of macroinvertebrates. Functional diversity declined nonlinearly with taxon loss, with the threshold response shifting to a rapid decline after 29.7%–60.0% taxa were lost. The sensitivities of ephemeropteran, plecopteran and trichopteran taxa (EPT) were negatively associated with their functional uniqueness, although this association was not detected when considering all macroinvertebrates. We identified 11 SRT and nine URT, but only one URT overlapped SRT. The association between species sensitivity and its functional uniqueness shapes functional decline patterns in response to taxon loss. Overlap patterns of SRT and URT offer novel insights into mechanisms underlying stress‐induced decline in functional diversity. The process of functional diversity decline in response to species loss caused by urbanisation also may be affected by species turnover or even compensated for by non‐native species in real world ecosystems. How functional diversity responds to species loss remains an open topic that needs to be cautiously addressed.